Animal Nutrition - McDonald, Peter, 1926-2018. (Harlow : Prentice Hall, 2002)
An introduction to the science and practice of animal nutrition. Animal Nutrition covers four main areas: the basic chemistry and biochemistry of feed constituents, digestion and metabolism; an evaluation of the energy and nutrient content of feedstuffs; the characteristics of feedstuffs; and tables on the composition of foods.
Previous ed.: Harlow : Longman, 1995.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Animal nutrition; Feeds